Cryosublimation Fractionating of Biological Material - Osetskiy, A. I.; Grischenko, V. I.; Snurnikov, A. S.; Shabanov, I. Ye.; Babijchuk, G. A. (Problems of Cryobiology and Cryomedicine, 2006)
The article presents the analysis of thermodynamic aspects of cryosublimation drying of biological objects. Composition of water fractions, obtained from biologicla objects during freeze-drying, is studied experimentally and their variation principles are determined. Peculiarities in technology realisation for molecular cryosublimation fractionating of biological objects as well as their perspective use in pharmacology and cosmetics production are discussed.